Subject pool recruitment procedures: organizing experiments with ORSEE - Greiner, Ben (Journal of the Economic Science Association, 2015)
This paper discusses aspects of recruiting subjects for economic laboratory experiments, and shows how the Online Recruitment System for Economic Experiments can help. The software package provides experimenters with a free, convenient, and very powerful tool to organize their experiments and sessions.